Geomagnetic observations and models - Mandea, Mioara; Korte, Monika; SpringerLink (Online service). (Dordrecht Springer, 2011)
This volume provides comprehensive and authoritative coverage of all the main areas linked to geomagnetic field observation, from instrumentation to methodology, on ground or near-Earth. Efforts are also focused on a 21st century e-Science approach to open access to all geomagnetic data, but also to the data preservation, data discovery, data rescue, and capacity building. Finally, modeling magnetic fields with different internal origins, with their variation in space and time, is an attempt to draw together into one place the traditional work in producing models as IGRF or describing the magnetic anomalies. Audience: This book will be of interest to researchers and scientists in geophysics and geomagnetism.
Part 1. Observation -- The global observatory network, new observatories -- Magnetic satellite missions -- Repeat station activities -- Instrument development -- Part 2. Data Improvements in data quality -- Overview data availability -- Magnetic indices -- Part 3. Modelling -- Modelling techniques: from global to regional -- Review IGRF models -- New core field models -- Interpretation of core field models -- Lithospheric field models, WDMAM -- Interpretation of lithospheric field -- Index.
Electronic reproduction.
Keywords: Geomagnetism -- Observations; Geomagnetism -- Mathematical models; Electronic books